Isolation and characterization of human adipose derived mesenchymal stem cells and production of GFP-labeled primary cells for in vivo tracking following transplantation - Pepper, Michael Sean (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.